2001
DOI: 10.1007/s005860100325
|View full text |Cite
|
Sign up to set email alerts
|

Porous tricalcium phosphate and transforming growth factor used for anterior spine surgery

Abstract: Harvesting autologous bone graft from the iliac crest is associated with considerable secondary morbidity. Bone graft substitutes such as porous ceramics are increasingly used for spinal surgery. This paper presents the results of an animal study in which β-tricalcium phosphate (β-TCP) bone substitutes were used for anterior spinal surgery in sheep and baboons. The presented baboon study also investigated the effect of impregnating the ceramic material with transforming growth factor (TGF). In the first study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(18 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Despite being 50±60 vol.-% ceramic (HA), [1] it combines high strength with toughness and can often repair itself without surgical intervention. However, trauma, disease, and congenital deformity can require the use of a graft to fill space to prevent fibrous tissue ingrowth during healing, restore cosmetic appearance, and to act as a scaffold for new bone formation.…”
Section: High-strength Apatitic Cement By Modification With A-hydroxymentioning
confidence: 99%
“…Despite being 50±60 vol.-% ceramic (HA), [1] it combines high strength with toughness and can often repair itself without surgical intervention. However, trauma, disease, and congenital deformity can require the use of a graft to fill space to prevent fibrous tissue ingrowth during healing, restore cosmetic appearance, and to act as a scaffold for new bone formation.…”
Section: High-strength Apatitic Cement By Modification With A-hydroxymentioning
confidence: 99%
“…Acrylic bone cement, Hap and TCP are currently used. The most frequently used is β-TCP because it is resorbable and osteoinductive (Gaasbeek et al, 2005;Steffen et al, 2001). β-TCP is resorbed in vivo by osteoclasts and replaced by new bone (Schilling et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, it is possible to facilitate bone formation in the bone-defect part by grafting porous materials into that part without administering growth factors or stem cells. 28) This study also demonstrated that a new bone was formed at the center of the defect, which does not commonly allow the formation of bones. Adhesive cells such as osteoblasts continue to function by adhering to materials that provide a foothold via proteins such as integrin.…”
Section: New Bone Formation and Apatite Orientation Inmentioning
confidence: 84%